Influence of Surface Processing on the Biocompatibility of Titanium - Wirsching, Kornelia (Materials (Basel), 2011)
Surface conditioning of titanium middle ear implants results in an improved biocompatibility, which can be characterized by the properties of fibroblasts cultured on conditioned surfaces. Titanium has been established as a favorable biomaterial in ossicular chain reconstruction. The epithelization of the surface of the implants is important for their integration and stable positioning in the middle ear. Mouse fibroblast cells were cultured on platelets made from pure Grade 2 titanium. Platelets that had been etched along their production process were compared to unetched platelets. The DNA in the cell nuclei was stained with DAPI and the actin filaments of the cytoskeleton were stained with FITC-conjugated phalloidin in order to analyze the cells grown on etched and unetched platelets by fluorescence microscopy. SEM (scanning electron microscopic) images were used to compare the surface structure of etched and unetched titanium platelets. There was a statistically significant increase of the area covered by the cytoplasm and increased actin expression by fibroblasts grown on the etched titanium platelets. In addition, the area of the platelets covered by nuclei on the etched platelets exceeded on average the one on unetched platelets, although this difference was not significant. The SEM pictures comparing unetched and etched titanium platelets showed a clear difference in surface structure. Surface conditioning of titanium implants improved the epithelization by fibroblasts and consequently etched titanium should be the preferred biomaterial for reconstructive middle ear surgery.